MANAJEMEN PROGRAM TAHFIDZ AL-QUR’AN DI MA’HAD AL-JAMI’AH - Nurhayati, Elis; Afriyani, Dessy; Dewi, Citra Kusuma (Managere: Indonesian Journal of Educational Management, 2022)
The purpose of this study was to describe the management of the Tahfidz Al-Qur'an Ma'had Al-jami'ah STIT program in Bekasi Regency. The research method used is a qualitative research in the form of descriptive evaluation, namely an evaluation evaluation that identifies educational values or practices by collecting information and analyzing data systematically. Based on the results of the study, the management of the Tahfidz Al-Qur'an Ma'had Al-jami'ah STIT Bekasi Regency program includes program planning, program implementation and program control. The planning stage begins with deliberation or meetings between supervisors, setting the planned goals, formulating methods, and implementing the implemented strategies. The implementation of the tahfidz program is carried out by determining the time and place of program implementation, the stages of program activities which include coordination with related parties and orientation between the committee, supervisors and tutors, as well as orientation among students participating in tahfidz Al Qur'an. And the system and pattern of program implementation which includes the person in charge, supervisor, examiner, and participants. The control of the tahfidz program is carried out by directing the students who are carried out after the planning and implementation are determined.